Effects of a Social Support Program on Stress and Spiritual Well – Being among Caregivers of End-Stage Cancer Patients - junma, sunsanee; Tipwareerom, Worawan; Juntarawijit, Yuwayong (NU Journal of Nursing and Health Sciences, 2022)
This study was a quasi - experimental research, using a two-group, pre-test/post-test design. The objective was to examine the effectiveness of a social support program on stress and spiritual well-being among caregivers of end-stage cancer patients. The samples were caregivers of end-stage cancer patients who received treatment in Nan Hospital. The samples were selected by purposive sampling, 30 persons each group divided in control group and experimental group .The control group received usual care and the experimental group received the social support program on stress and spiritual well-being among the caregivers of end-stage cancer patients for12 weeks. The research instruments consisted of personal data, spiritual well – being assessment stress assessment with reliability 0.85 and 0.89 respectively. Data were analyzed by using descriptive statistics, independent samples t-test and paired samples t-test. The results showed that the experimental group had the mean score of preoperative stress level was significantly decreased (p < .001). After receiving the program, the caregivers well-being score of the experimental group level was significantly increased (p < .001). After receiving the program, the caregivers role stress score of the experimental group lower than before receiving the program (p < .001). After receiving the program, the caregivers well-being score of the experimental group was higher than before receiving the program (p < .001). The results of study indicate that the Social Support Program could has positive effect on stress and spiritual well-being among caregivers of end-stage cancer patients . Therefore, that program can be use in nursing practice to enhance more effective on adaptation among caregivers end-stage to reduce stress and increase spiritual well-being.